Influence of Low-Magnitude High-Frequency Vibration on Bone Cells and Bone Regeneration - Steppe, Lena; Liedert, Astrid; Ignatius, Anita; Haffner-Luntzer, Melanie (Frontiers in Bioengineering and Biotechnology, 2020)
Bone is a mechanosensitive tissue for which mechanical stimuli are crucial in maintaining its structure and function. Bone cells react to their biomechanical environment by activating molecular signaling pathways, which regulate their proliferation, differentiation and matrix production. Bone implants influence the mechanical conditions in the adjacent bone tissue. Optimizing their mechanical properties can support bone regeneration. Furthermore, external biomechanical stimulation can be applied to improve implant osseointegration and accelerate bone regeneration. One promising anabolic therapy is vertical whole-body low-magnitude high-frequency vibration (LMHFV). This form of vibration is currently extensively investigated to serve as an easy-to-apply, cost-effective and efficient treatment for bone disorders and regeneration. This review aims to provide an overview of LMHFV effects on bone cells in vitro and on implant integration and bone fracture healing in vivo. In particular, we review the current knowledge on cellular signaling pathways which are influenced by LMHFV within bone tissue. Most of the in vitro experiments showed that LMHFV is able to enhance mesenchymal stem cell (MSC) and osteoblast proliferation. Furthermore, osteogenic differentiation of MSCs and osteoblasts were shown to be accelerated by LMHFV, whereas osteoclastogenic differentiation was inhibited. Furthermore, LMHFV increased bone regeneration during osteoporotic fracture healing and osseointegration of orthopedic implants. Important mechanosensitive pathways mediating the effects of LMHFV might be the Wnt/beta-catenin signaling pathway, the estrogen receptor signaling pathway and cytoskeletal remodeling.